Raw Material Sources of Uzbekistan’s Industry and Their Location - Xalimov , Umidjon (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This scientific article analyzes the main raw material sources of Uzbekistan’s industry, their significance in the economy, and the factors influencing the territorial placement of industrial sectors. It also provides information about industrial centers formed on the basis of fuel and energy resources, metallurgy, chemical industry, and agricultural raw materials.The study highlights the role of transport, labor resources, energy sources, and consumer factors in the location of industrial enterprises.